Pengaruh E-Service Quality Terhadap E-Customer Loyalty Dimediasi Oleh E-Customer Satisfaction Pada Jasa Titip Online Alat Modifikasi Mobil Diesel @2GDVABIRU - Ganesha, Alvalif Ilham (UNIB Press, 2023)
The purpose of this study was to examine the effect of e-service quality on e-customer loyalty which is mediated by e-customer satisfaction on the service of online diesel car modified item consignment service @2gdvabiru in Indonesia. The sampling technique in this study used a purposive sampling technique. The data collection technique uses a questionnaire that is distributed online via Instagram. Measurement research in this questionnaire consists of 16 questions to respondents. The number of samples is 116 Instagram account users @2gdvabiru in Indonesia. The analysis tool used is PLS-SEM with the help of SmartPls version 3.3.9. The results showed that (1) electronic service quality had a significant positive effect on electronic customer satisfaction; (2) electronic service quality had a significant positive effect on electronic customer satisfaction; (3) electronic customer satisfaction had a significant positive effect on electronic service quality; (4) e-service quality has a significant positive effect on e-customer loyalty mediated by e-customer satisfaction; Keyword: E-customer loyalty; E-customer satisfaction; E-service quality